Estrous Performance of Etawah Crossbred Goats Following Different Estrous Synchronization Methods - Solihati, Nurcholidah; Rasad, Siti Darodjah; Winangun, Kikin; Toha, Toha (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
The objective of the research was to determine the estrous profile of Etawah Crossbred goats after estrous synchronization with different methods. Eighteen does aged 12-24 month old were divided in three groups to receive estrous synchronization treatments (T1 = 14 days intravaginal implant of 60 mg of progesterone (MPA), T2 = two times injection of 5 mg PGF2Î± (lutalyse) in 11 days interval, and T3 = 10 days of intravaginal implant of 60 mg of progesterone (MPA) + injection of 5 mg PGF2Î± 48 hours before removal) with six replications. The parameters consisted of estrous behaviour, changes in size and colour of vulva, and duration of estrus when the number of superficial and keratin cells were dominating in the vaginal mucus cell. Data from estrous behaviour and score of vulvar colour was analyzed using Kurkal Wallis test, while onset of estrus, size of vulva slit and estrous duration was analyzed using ANOVA and Duncan test. The result showed that estrous behaviour and changes in color and size of vulva were not significantly different, but estrous duration was significantly different. Estrous duration in T1 (31.30 hour) and T2 (31.10 hour) was significantly longer than that of T3 (11.36 hour). It is concluded that different methods of estrus synchronization affected estrous quality equally but it affected the estrous duration differently based on vaginal mucus cells. Treatment implant vaginal sponge content progesterone for 14 days and double injection of PGF2Î± with 11-day interval given longest estrous duration.